Review of improvements in upper limb function with balance training and adjunct intervention in stroke survivors - Goh, Candace Xiao Huey; Ahmedy, Fatimah; Yin, Khin Nyein (Science, Engineering and Health Studies, 2024)
Balance is one of the main factors influencing the ability to walk. Various rehabilitation strategies have been developed to help stroke survivors regain functional ability. However, limited evidence is available on the effects of balance training on improving upper limb function. The goal of this review was to summarize the most recent research on the benefits of balance training and adjunct intervention for upper limb function in stroke survivors. Using the search phrases “stroke” AND “balance training” AND “hand function", the PubMed and Scopus databases were used to find relevant articles. Only those published in English were chosen, while the study included randomized controlled trials held between 2012 and 2021 involving stroke survivors aged 18 and above who underwent balance training. Dissertations, case studies, and review articles were excluded. Overall, 28 of 237 articles were eligible after screening based on the eligibility criteria. Ten articles were selected for the review. The intervention and control groups had 156 and 154 participants, respectively. Core muscle exercises; adjunct interventions such as virtual reality, action observation, and resistance training; and comparisons with combination therapy were among the main types of balance training. The Fugl-Meyer assessment upper extremity and Wolf motor function test were the primary outcome measures used to evaluate upper limb function. Of the ten trials chosen, six utilized combination therapy and demonstrated noticeable improvements in upper limb function.